Control of the seed rice nematode Aphelenchoides besseyi - Silveira, Salima G. P. da; Curi, Sérgio M.; Leite, Norberto; Camargo, Otávio B. de A.; Brignani Neto, Francisco; Arruda, Hermano V. de (Pesquisa Agropecuaria Brasileira, 2014)
Six trials were carried out at Lorena and Pindamonhangaba, SP, Brazil, to study the control of the rice nematode Aphelenchoides besseyi Christie 1942, for irrigated conditions. Some chemicals and one thermal treatment were effective in decreasing nematode density; nevertheless, there was no association with yield increases. The cultivars IR 841, IAC 435, IAC 120 and IAC 899 were very tolerant to nematode with yields prominence of IAC 899.
Keywords: density; tolerance; chemical treatments; thermal treatments; populational level